Scaled MP3 non-covalent interaction energies agree closely with accurate CCSD(T) benchmark data - Pitonák, Michal; Neogrády, Pavel; Cerný, Jirí; Grimme, Stefan; Hobza, Pavel (Chemphyschem, 2009)
Scaled MP3 interaction energies calculated as a sum of MP2/CBS (complete basis set limit) interaction energies and scaled third-order energy contributions obtained in small or medium size basis sets agree very closely with the estimated CCSD(T)/CBS interaction energies for the 22 H-bonded, dispersion-controlled and mixed non-covalent complexes from the S22 data set. Performance of this so-called MP2.5 (third-order scaling factor of 0.5) method has also been tested for 33 nucleic acid base pairs and two stacked conformers of porphine dimer. In all the test cases, performance of the MP2.5 method was shown to be superior to the scaled spin-component MP2 based methods, e.g. SCS-MP2, SCSN-MP2 and SCS(MI)-MP2. In particular, a very balanced treatment of hydrogen-bonded compared to stacked complexes is achieved with MP2.5. The main advantage of the approach is that it employs only a single empirical parameter and is thus biased by two rigorously defined, asymptotically correct ab-initio methods, MP2 and MP3. The method is proposed as an accurate but computationally feasible alternative to CCSD(T) for the computation of the properties of various kinds of non-covalently bound systems.
Keywords: termodynamika; vodíková vazba; Models, Chemical; Thermodynamics; chemické modely; algoritmy; nukleotidy; Algorithms; Nucleotides; Hydrogen Bonding